Indications and safety of plastibell circumcision in children - Ofoha, Chimaobi G.; Babangida, Sankey J.; Nabasu, Lemech E.; Dakum, Nuhu K. (International Surgery Journal, 2018)
Background: Circumcision is the surgical excision of the prepuce. It is an ancient practice with roots in religion and cultural practices. Indications for circumcision include phimosis, paraphimosis, balanoposthitis, balanitis, Balanitis xerotica obliterans and trauma to the prepuce. Various methods of circumcision have been described; Flap method, Gomco, Smartklamp and Plastibell etc. The Plastibell works by the clamp principle. The aim of this study is to determine the indications and safety of circumcision using the Plastibell device. Methods: This was a prospective study carried out in two hospitals for a period of one year. The parents were counselled on the procedure. The children were assessed to identify conditions that might adversely affect the outcome. The age of the babies, indication, size of Plastibel and complications were recorded. Results: Two hundred and forty-five infants were enrolled into the study. The age range was seven to one hundred and sixty-eight days. Majority of the circumcision was done in the first thirty days of life (63.8%). Indication for circumcision was religion (n=245, 100%) in all cases. The range of the Plastibel size used was 1.1 to 1.5. Ten of the children had complications representing 4.1%. The commonest complication was retained Plastibel, constituting 50% of the overall complications followed by bleeding (30%). Conclusions: Religion was the indication for the circumcisions and most of the circumcisions were done in the neonatal period. The Plastibell method of circumcision is associated with minor remediable complications when performed by trained personal.